2021
DOI: 10.3390/antiox10081190
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular SGLT1 Protein Expression Correlates with the Extent of Myocardial Nitro-Oxidative Stress in Rats with Pressure and Volume Overload-Induced Heart Failure

Abstract: Myocardial sodium-glucose cotransporter 1 (SGLT1) has been shown to be upregulated in humans with heart failure (HF) with or without diabetes. In vitro studies have linked SGLT1 to increased nitro-oxidative stress in cardiomyocytes. We aimed to assess the relation between left ventricular (LV) SGLT1 expression and the extent of nitro-oxidative stress in two non-diabetic rat models of chronic heart failure (HF) evoked by either pressure (TAC, n = 12) or volume overload (ACF, n = 12). Sham-operated animals (Sham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
3
4
0
Order By: Relevance
“…We also reported that canagliflozin blunts oxidative stress in non-diabetic rats with acute myocardial ischemia-reperfusion injury [80]. In line with these, we showed that LV SGLT1 expression is upregulated in non-diabetic rats with HF, irrespective of whether chronic pressure (transverse aortic constriction, TAC) or volume (aortocaval fistula) overload was the underlying pathophysiology [60]. The expression of SGLT1 showed a robust correlation with the extent of myocardial nitro-oxidative stress in rats with HF [60].…”
Section: Role Of Myocardial Sglt1 Under Non-diabetic Conditionssupporting
confidence: 81%
See 4 more Smart Citations
“…We also reported that canagliflozin blunts oxidative stress in non-diabetic rats with acute myocardial ischemia-reperfusion injury [80]. In line with these, we showed that LV SGLT1 expression is upregulated in non-diabetic rats with HF, irrespective of whether chronic pressure (transverse aortic constriction, TAC) or volume (aortocaval fistula) overload was the underlying pathophysiology [60]. The expression of SGLT1 showed a robust correlation with the extent of myocardial nitro-oxidative stress in rats with HF [60].…”
Section: Role Of Myocardial Sglt1 Under Non-diabetic Conditionssupporting
confidence: 81%
“…In line with these, we showed that LV SGLT1 expression is upregulated in non-diabetic rats with HF, irrespective of whether chronic pressure (transverse aortic constriction, TAC) or volume (aortocaval fistula) overload was the underlying pathophysiology [60]. The expression of SGLT1 showed a robust correlation with the extent of myocardial nitro-oxidative stress in rats with HF [60]. Mouse neonatal cardiomyocytes with genetically ablated SGLT1 are resistant to in vitro hypertrophic stimuli, whereas mice with global SGLT1 knockout are protected from the development of pathological LV hypertrophy in response to chronic pressure overload induced by TAC [59].…”
Section: Role Of Myocardial Sglt1 Under Non-diabetic Conditionssupporting
confidence: 80%
See 3 more Smart Citations